2013
DOI: 10.1002/prot.24324
|View full text |Cite
|
Sign up to set email alerts
|

Substrate versus inhibitor dynamics of P‐glycoprotein

Abstract: By far the most studied multidrug resistance protein is P-glycoprotein. Despite recent structural data, key questions about its function remain. P-glycoprotein (P-gp) is flexible and undergoes large conformational changes as part of its function and in this respect, details not only of the export cycle, but also the recognition stage are currently lacking. Given the flexibility, molecular dynamics (MD) simulations provide an ideal tool to examine this aspect in detail. We have performed MD simulations to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 66 publications
8
34
0
Order By: Relevance
“…In fact, many previous studies have also noted the asymmetric closing/opening pathway of NBDs, including P-gp, Sav1866, MalK 2 , FbpC, MsbA, and MJ0796, where one ABP site closes/opens first, followed by the other ABP site. 39,[41][42][43][44][45][46] Above all, the free energy maps could be roughly divided into three regions: (1) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Even though the Mg-ATP can trigger the closure of MalK 2 , the complete conformational transition from the open to the closed state could not be observed: the protein structure was trapped in a quasistable state with the mismatched interaction between the two D-loops, and thus ATP molecules were not sandwiched between the Walker A and signature motif. The PCA ( Figure 6-(b)) indicates a not-well-coupled movement between HSD and CSD in the right-hand side monomer (colored in cyan), which may be responsible for the mis-dimerizing.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, many previous studies have also noted the asymmetric closing/opening pathway of NBDs, including P-gp, Sav1866, MalK 2 , FbpC, MsbA, and MJ0796, where one ABP site closes/opens first, followed by the other ABP site. 39,[41][42][43][44][45][46] Above all, the free energy maps could be roughly divided into three regions: (1) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Even though the Mg-ATP can trigger the closure of MalK 2 , the complete conformational transition from the open to the closed state could not be observed: the protein structure was trapped in a quasistable state with the mismatched interaction between the two D-loops, and thus ATP molecules were not sandwiched between the Walker A and signature motif. The PCA ( Figure 6-(b)) indicates a not-well-coupled movement between HSD and CSD in the right-hand side monomer (colored in cyan), which may be responsible for the mis-dimerizing.…”
Section: Resultsmentioning
confidence: 99%
“…In recent work, molecular dynamics studies of daunorubicin and the QZ59 inhibitors have been reported 70 that suggest that inhibitors like QZ59-RRR and QZ59-SSS may inhibit P-gp by preventing NBD closure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the problem seems to probably reside elsewhere, namely in the polyspecificity of the drug‐binding pocket. From structural data, the high structural flexibility described for P‐gp suggested the existence of multiple redundant drug‐binding sites that recognize substrates through an induced‐fit mechanism . However, the specific mode by which efflux can be modulated (competitive, noncompetitive, or allosteric) is still controversial.…”
Section: Efflux Modulation: Past Present and Futurementioning
confidence: 99%